Optimization of Heat Integration Systems Considering Multiple Utilities, Organic Rankine Cycles, and Rigorous Thermodynamic Property Calculations - Corrêa, Victor Hugo; Vassoler, Carlos Henrique; Costa, Caliane Bastos Borba; Ravagnani, Mauro Antonio da Silva Sá; Pavão, Leandro Vitor (Industrial & engineering chemistry research, 2025)
Energy integration is a widely studied subject in Process Synthesis. An interesting solution in heat integration is the coupling of heat recovery systems to Organic Rankine Cycles (ORCs). The relatively low operating temperature of these cycles enables heat recovery from low-temperature hot streams by conversion to electricity for revenue. However, the inclusion of ORC-related equations in Heat Exchanger Network (HEN) models increases the problem’s complexity. This study tackles the problem using an implicit heat integration method via a Pinch Operator with rigorous calculation of thermodynamic properties (enthalpy, entropy, etc.). Two case studies are approached here. In the first case study, efficiencies of approximately 14% were achieved for an n-pentane cycle. In the second case study, when isentropic pressure changes are considered, efficiencies for n-pentane, n-hexane, and n-perfluoro-pentane were found to be ca. 12%, 14%, and 10%, respectively. Additionally, the study includes detailed cost–benefit analyses for each condition in both case studies.